High‐grade dysplasia/carcinoma in situ of the bile duct margin in patients with surgically resected node‐negative perihilar cholangiocarcinoma is associated with poor survival: a retrospective study. (3rd July 2017) - Higuchi, Ryota; Yazawa, Takehisa; Uemura, Shuichiro; Izumo, Wataru; Furukawa, Toru; Yamamoto, Masakazu
Abstract: Background: The clinical relevance of a high‐grade dysplasia/carcinoma in situ (HD/CIS)‐positive bile duct margin in perihilar cholangiocarcinoma (PHC) is unclear. We evaluated the surgical outcomes of PHC patients with HD/CIS. Methods: Clinicopathological data of 163 consecutive patients who underwent resection of PHC between 2004 and 2013 were analyzed retrospectively. Results: Postoperative states included curative resection (R0) with free margins in 113 patients, non‐curative resection with HD/CIS (R1‐HD/CIS) in 22 patients, and non‐curative resection with any invasive carcinoma margin in 28 patients. Multivariate analyses in the entire cohort showed that lymph node metastasis (hazard ratio [HR] 1.91), distant metastasis (HR 3.87), and non‐curative resection with any invasive carcinoma margin (vs. R0; HR 2.06) were significant independent prognosticators. However, in node‐negative and distant metastasis‐negative PHC patients, histology (HR 2.97), R1‐HD/CIS (vs. R0; HR 2.31), and non‐curative resection with any invasive carcinoma margin (vs. R0; HR 5.33) were significant independent prognosticators. The 2‐ and 5‐year disease‐specific survival rates in node‐negative and distant metastasis‐negative PHC patients with R1‐HD/CIS margins were lower compared with those in patients with R0 margins (2‐year, 76.7% vs. 84.3%; 5‐year, 37.5% vs. 69.3%; P = 0.026). Conclusions: R1‐HD/CIS should be avoided in patients undergoing surgery for node‐negative and distant metastasis‐negative PHC. Abstract : Highlight In this retrospective study including the largest cohort of perihilar cholangiocarcinoma patients to date, Higuchi and colleagues demonstrated that the surgical outcomes of patients with node‐negative and distant metastasis‐negative perihilar cholangiocarcinoma are significantly worse after non‐curative resection with high‐grade dysplasia/carcinoma in situ ‐positive margins than after R0 resection with negative margins.